2007
DOI: 10.1021/om061132p
|View full text |Cite
|
Sign up to set email alerts
|

Endo-Effect-Driven Regioselectivity in the Cyclopalladation of (S)-2-tert-Butyl-4-phenyl-2-oxazoline

Abstract: Direct cyclopalladation of (S)-2-tert-butyl-4-phenyl-2-oxazoline using palladium acetate in acetic acid or acetonitrile provided a mixture of two isomeric compounds, the endo μ-AcO dimeric complex with a C(sp3)−Pd bond and the corresponding exo derivative with a C(sp2)−Pd bond, with the former being the major product. The μ-AcO dimeric complexes were converted to the corresponding μ-Cl analogues 3 and 4 by treatment with LiCl in acetone; the latter compounds were transformed to the corresponding PPh3 adducts 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 78 publications
3
28
1
1
Order By: Relevance
“…It is well known that, in general, activation of aromatic (sp 2 )C-H bonds proceeds more easily than that of aliphatic (sp 3 )C-H bonds [29]. On the other hand, exclusive or predominant formation of endo palladacycles over exo isomers in solutions has been well documented for imines and oxazolines [30][31][32][33][34]. It was found that oxazoline 1j reacted with Pd(OAc) 2 on SiO 2 followed by treatment with LiCl to form exclusively endo-2j in 64% yield with no traces of the exo isomer (Scheme 8).…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that, in general, activation of aromatic (sp 2 )C-H bonds proceeds more easily than that of aliphatic (sp 3 )C-H bonds [29]. On the other hand, exclusive or predominant formation of endo palladacycles over exo isomers in solutions has been well documented for imines and oxazolines [30][31][32][33][34]. It was found that oxazoline 1j reacted with Pd(OAc) 2 on SiO 2 followed by treatment with LiCl to form exclusively endo-2j in 64% yield with no traces of the exo isomer (Scheme 8).…”
Section: Resultsmentioning
confidence: 99%
“…Because of the tert-butyl substituent in 1, there is no hydrogen atom available for an imine-enamine rearrangement. However, formation of a dinuclear palladacycle has been reported from a similar imine by proton abstraction from a methyl substituent of the tert-butyl groups with palladium acetate and lithium chloride, but the cyclopalladation does not occur in the reaction with palladium chloride [8]. Accordingly, we synthesized the new complex trans-[PdCl 2 (2,4,6-Me 3 C 6 H 2 CH 2 N@CH t Bu) 2 ] (2) by reacting the ligand 1 with [PdCl 2 (C 6 H 5 CN) 2 ] in dichloromethane [9].…”
Section: Imines Containing a Benzyl Functionmentioning
confidence: 99%
“…The structures of the complexes were supported by 1 H, 13 C, DEPT, COSY and HSQC NMR spectra. Coordination of the Pd atom with the N atom of the heterocycle was supported by the wavelength shift of the C@N absorption band in the IR spectra [5,7] of the complexes [m 1666 cm À1 for PdCl 2 (1) 2 and 1643 cm À1 for PdCl 2 (2) 2 ] compared to that of the corresponding ligands (m 1677 cm À1 for 1 and 1666 cm À1 for 2). According to 1 H and 13 C NMR spectra of PdCl 2 (1) 2 prepared by the reaction of ligand 1 with Pd(OAc) 2 in MeCN (1:1 ratio, 66°C, 6 h) followed by reaction with LiCl in acetone, the coordination complex was a mixture of two isomers in a ratio of ca.…”
Section: Introductionmentioning
confidence: 97%
“…A variety of monooxazoline-derived five-membered exo-and endo -palladacycles with a central chirality have been described; they contain either the (sp 3 )C-Pd or (sp 2 )C-Pd bond [5]. C-Chiral oxazoline-based six-membered exo-and endo-palladacycles with a (sp 2 )C-Pd bond have also been reported (A-C, Chart 1) [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation